Architectural correspondence, architectural misting, and innovation: New perspectives. (7th January 2020) - Burton, Nicholas; Sarpong, David; O'Regan, Nicholas
Abstract: The relationship between innovation, product design, and industry co‐evolution remains under‐theorized. This article discusses gaps in knowledge and introduces the contributing papers in this special issue.